2013
DOI: 10.4161/viru.24930
|View full text |Cite
|
Sign up to set email alerts
|

Galleria mellonellalarvae as an infection model for group A streptococcus

Abstract: Group A streptococcus is a strict human pathogen that can cause a wide range of diseases, such as tonsillitis, impetigo, necrotizing fasciitis, toxic shock, and acute rheumatic fever. Modeling human diseases in animals is complicated, and rapid, simple, and cost-effective in vivo models of GAS infection are clearly lacking. Recently, the use of non-mammalian models to model human disease is starting to re-attract attention. Galleria mellonella larvae, also known as wax worms, have been investigated for modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
153
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 56 publications
3
153
0
17
Order By: Relevance
“…End points in G. mellonella infection models include survival rate, which can be assessed up to 5 d post infection, or longer with some fungal pathogens, facilitating the calculation of a maximum half lethal dose (LD50); expression of antimicrobial proteins in response to infection; production of lactate dehydrogenase as a marker of cell damage and biophotonic imaging to measure proliferation of bioluminescent microorganisms responsible for larval infection. [33][34][35][36][37] A pathological scoring system was recently proposed by Loh et al 38 in which an assessment of larval mobility, cocoon formation, melanisation and survival was used to assess larval health.…”
Section: G Mellonella To Study Toxinsmentioning
confidence: 99%
“…End points in G. mellonella infection models include survival rate, which can be assessed up to 5 d post infection, or longer with some fungal pathogens, facilitating the calculation of a maximum half lethal dose (LD50); expression of antimicrobial proteins in response to infection; production of lactate dehydrogenase as a marker of cell damage and biophotonic imaging to measure proliferation of bioluminescent microorganisms responsible for larval infection. [33][34][35][36][37] A pathological scoring system was recently proposed by Loh et al 38 in which an assessment of larval mobility, cocoon formation, melanisation and survival was used to assess larval health.…”
Section: G Mellonella To Study Toxinsmentioning
confidence: 99%
“…AB5075 bacteria previously exposed to AB-Army1 phage displayed a translucent phenotype similar to that of epsA and ptk capsule mutants. Because A. baumannii epsA and ptk mutants have been shown to be attenuated in an animal model (34), we hypothesized that translucent AB5075 bacteria previously exposed to AB-Army1 phage would be less virulent than wild-type AB5075 bacteria in a G. mellonella wax worm model of infection (35,49). Evaluation of AB5075, AB-Army1-exposed AB5075, AB5075P, AB5075 epsA::Tn5, and AB5075 ptk:: Tn5 in the worm model confirmed that all four translucent strains were avirulent in comparison to capsule-positive AB5075 (Fig.…”
mentioning
confidence: 99%
“…Entretanto, existem diversos modelos bem estabelecidos em ratos e macacos que provaram ser válidos para avaliar a infecção por S. pyogenes. Com as dificuldades encontradas para utilização de mamíferos, como aprovação ética e alto custo, cresceu a busca por modelos alternativos (LOH et al, 2013). Abranches et al (2011) observaram que a ausência do gene cnm, codificador de uma proteína de ligação à laminina e ao colágeno, resultou na atenuação da virulência de S. mutans.…”
Section: Galleria Mellonella Como Modelo De Infecção Bacteriana Por Sunclassified
“…Todas as bactérias com mutação apresentaram menor virulência do que as originais, demonstrando que os genes avaliados têm funções importantes na infecção por S. pyogenes (OLSEN et al, 2011). Loh et al (2013) observaram o efeito da temperatura na mortalidade das larvas, após infecção com S. pyogenes. As larvas mantidas a 28°C apresentaram DL 50 (dose letal capaz de matar 50% do grupo de larvas testado) significativamente maior do que às mantidas a 37°C, mostrando a influência da temperatura na taxa de mortalidade das larvas infectadas.…”
Section: Galleria Mellonella Como Modelo De Infecção Bacteriana Por Sunclassified
See 1 more Smart Citation